(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Auditory exostoses are bone masses located in the external auditory canal. Currently, most researchers agree that the environment (especially water temperature, but also atmospheric temperature and wind action) plays a pivotal role in the development of exostosis. Exostoses are a condition in which the external auditory canal becomes stenotic secondary to hyperplastic bone formation. Also known as surfers ear, exostoses are thought to be a reactive process from repeated stimulation by cold water because it occurs commonly in populations such as beach lifeguards and surfers. Exostoses are usually asymptomatic and discovered on routine otoscopy. Rarely, exostoses become sufficiently obstructive to impair hearing or cause recurrent otitis externa. Exostoses are almost always bilateral, symmetric, and occurring in the medial portion of the external auditory canal. Tthe authors report a case of bilateral external auditory canal exostoses in an adult male treated with surgical excision. DOI: http://dx.doi.org/10.3329/bjo.v18i1.10428 Bangladesh J Otorhinolaryngol 2012; 18(1): 91-95